MENINGKATKAN PERILAKU KEWARGAAN ORGANISASI BAGI GURU DAN TENAGA KEPENDIDIKAN - Hardianto, Hardianto (Idaarah: Jurnal Manajemen Pendidikan, 2019)
In carrying out their duties, teachers and education staff must have Organizational Citizenship Behavior (OCB) behavior. With the behavior of teachers and OCB education personnel, they will display behavior that exceeds the basic tasks assigned to them. This article uses the library study method. Data analysis using descriptive techniques. From the research results it is known that OCB behavior from teachers and education staff will make the school realize its vision well. Some of the factors that influence OCB teacher behavior are appreciation, job satisfaction, motivation, commitment and loyalty. Therefore the principal and the education office must pay attention to these factors so that the behavior of the teacher’s OCB can always be improved.